Pubic Hair Removal and Sexual Behavior: Findings from a Prospective Daily Diary Study of Sexually Active Women in the United States. (13th December 2012) - Herbenick, Debby; Hensel, Devon; Smith, Nicole K.; Schick, Vanessa; Reece, Michael; Sanders, Stephanie A.; Fortenberry, J. Dennis
ABSTRACT Introduction. Pubic hair removal is prevalent among women in the United States. However, most studies related to pubic hair removal are based on cross‐sectional surveys and retrospective recall. Aim. The purpose of this research was to, in a prospective event‐level daily diary study, assess demographic, affective, relational, situational, and behavioral factors related to women's pubic hair removal. Method. Data collection occurred as part of a 5‐week prospective, Internet‐based daily diary study. Main Outcome Measures. Age; Affective predictors (positive mood, negative mood, feeling interested in sex, feeling in love); Relational predictors (partner support, partner negativity, partner type, partner gender); Situational predictors (any vaginal symptoms, use of any vaginal hygiene products; having applied any creams to the genitals); Behavioral variables (penile–vaginal sex, penile–anal sex, had finger inserted into vagina, had clitoris stimulated with fingers, inserted toy into vagina, used vibrator on clitoris, inserted finger into anus, inserted toy into anus, duration of penetration, intensity of penetration). Results. A total of 2, 453 women ages 18 to 68 (mean age 32.69) completed the study, contributing 49, 287 total diaries (mean per person 24.5; standard deviation 10.3, median 30); 15.2% of all days (N = 7, 362) involved pubic hair waxing or shaving, with the vast majority of hair removal days involving shaving (N = 7, 302; 99%). Pubic hair removal was significantly associated with younger age, a greater interest in sex, vaginal fingering, finger–clitoral stimulation, having a casual sex partner, using vaginal hygiene products, and applying cream to the genitals. Hair removal was marginally associated with longer duration of vaginal penetration. Conclusions. These findings provide greater insight into the factors associated with women's pubic hair removal and their sexual experiences on a day‐to‐day level. Clinical and educational implications are discussed. Herbenick D, Hensel D, Smith NK, Schick V, Reece M, Sanders SA, and Fortenberry JD. Pubic hair removal and sexual behavior: Findings from a prospective daily diary study of sexually active women in the United States. J Sex Med 2013;10:678–685.